Promoting Healthy Nutrition in Preschool Educational Institutions - Fozilova Nodira Jonibekovna (Genius Publishing Group, 2023)
This article discusses the rules of proper nutrition in preschool education organizations, the main tasks of organizing healthy nutrition, and the requirements for creating menus.
Keywords: proper nutrition; product; food; vitamin